Effect Nutrient "N" Dose on Growth and Protein Content of Napier Pakchong Grass and Zanzibar Napier Grass - M Abror; Muhammad Tsamrotul Fuadi (Nabatia, 2022)
The purpose of this study was to determine the effect of the dose of nutrient N on the growth and protein content of napier pakchong grass and napier zanzibar grass. The experiment was arranged using a randomized block design (RAK) with a single factor, namely the dose of N fertilizer on two different types of napier grass, including (1) The dose of N fertilizer was 60 kg/ha on the type Napier Pakchong Grass (2) The dose of N fertilizer is 150 kg/ha on the type of Napier Pakchong Grass. (3) The dose of N fertilizer is 240 kg/ha on the type of Napier Pakchong Grass. (4) The dose of N fertilizer is 60 kg/ha on the type of Zanzibar Napier Grass (5) The dose of N fertilizer is 150 kg/ha on the type of Napier Zanzibar Grass (6) The dose of N fertilizer is 240 kg/ha on the type of Napier Zanzibar Grass. The results of this study showed that there was a very significant response to the variable height of the plant throughout the observation period, the observation of the number of tillers and the number of leaves showed a significant response at the age of 14, 28 and 70 days after planting. The stem diameter showed a significant response only at the age of 14 days after planting and also gave a very significant response to the wet weight observation variable but did not give an unsignificant response to the dry weight observation and protein content test.